Outcomes of Non-Operatively Treated Elbow Ulnar Collateral Ligament Injuries in Professional Baseball Players by Magnetic Resonance Imaging Tear Grade and Location. Issue 7 (29th July 2019) - Chauhan, Aakash; Chalmers, Peter Nissen; McQueen, Peter Douglas; Camp, Christopher L.; Potter, Hollis G.; Ciccotti, Michael G.; D'Angelo, John; Hoenecke, Heinz R.; Erickson, Brandon J.; Fealy, Stephen; Fronek, Jan
Objectives: Evaluate the relationship of 1) MRI tear grade and 2) injury location with outcomes for non-operatively treated elbow ulnar collateral ligament (UCL) injuries in professional baseball players. Methods: 544 professional baseball players were identified from the MLB Health and Injury Tracking System (HITS) that were treated non-operatively for their UCL injuries from 2011-2015. Of these players, 237 MRI's were directly available for review by an independent, expert musculoskeletal radiologist who evaluated the grade (Grade I -edema, II-partial tear, III-complete tear) and location of the tears (humeral, ulnar, both-sided). Player demographics and outcomes including return to throwing (RTT), return to play (RTP), failed non-operative treatment leading to UCL reconstruction (UCLR), and Kaplan-Meier survivorship analysis of the native UCL to re-injury or surgery based on MRI grade and tear location was measured. A multivariate analysis adjusting for age, MRI grade, tear location, and level of play (Major = MLB; Minor = MiLB) was also performed. Results: The average age of all players was 22.5 years, 90% played at the MiLB level, and 84% were pitchers. The radiologist's MRI injury grade was distributed as follows: Grade I (36%), Grade II (49%), and Grade III (15%) injuries. The tear locations were distributed as follows: humeral (65%), ulnar (13%), and both-sided (22%). There were no statistically significant differences in RTT, RTP, and UCLR by grade or tear location. However, objectively, ulnar-sided tears had the lowest RTT (81%) and RTP (42%). The ulnar (58%) and both-sided (60%) tears also had an objectively higher rate of UCLR compared to humeral sided tears (51%, p=0.441). The survivorship analysis showed a consistent decline over time with increasing MRI grade. By location, humeral tears had the highest survivorship (1 yr = 51%; 2 yr = 44%). However, there was no statistically significant differences in survivorship for either grade or location. Multivariate analysis measured the likelihood of not returning to play as 3 times higher [95% CI: 1-9.3; p=0.044] for older players (>25) compared to younger players. The likelihood of having re-injury or UCLR after non-operative treatment failed was almost 6 times higher [95% CI: 1.5-21.7; p=0.012] for MLB players as opposed to MiLB players. MRI grade and tear location were not significantly predictive of returning to play, re-injury, or surgery. Conclusion: This is the largest study to evaluate the prognostic relationship of MRI injury grade and tear location with outcomes for non-operatively treated elbow UCL tears in professional baseball players. Lower MRI grade and humeral location were objectively associated with a higher RTT, higher RTP, lower UCLR, and higher survival compared to higher grade, and ulnar or both-sided tears. Older age (>25) had a significantly higher likelihood of not returning to play after non-operative treatment. Competing at the MLB level had a higher likelihood of re-injury or having UCLR. Based on this study, non-operative treatment of UCL injuries will likely be more successful in younger players, lower grade tears, and humeral-sided injuries.